Inclusive human development and governance: a panel data analysis of selected Asian countries - Stylianou, Tasos; Nasir, Rakia; Waqas, Muhammad; Nisar, Uzma (Frontiers in Political Science, 2025)
This study examines the role of governance in promoting inclusive human development across twenty-four selected Asian countries by analyzing panel data from 2010 to 2022. The World Bank’s inequality-adjusted human development index is used as a measure of inclusive human development. Six governance indicators are analyzed as independent variables in each regression model, along with three control variables: trade openness, competitiveness, and developmental expenditure. The results of panel unit root tests, LLC, and ADF show that all the variables have the same order of integration. Ten different regression analyses are conducted, including six indicators, three dimensions, and an overall index. Principal component analysis is used to develop dimensions and an overall governance index. The findings of the study reveal a significant relationship between most of the governance indicators and inclusive human development in selected Asian countries. The study shows that political stability, governance effectiveness, rule of law, and control of corruption promote inclusive human development in selected Asian countries. However, voice, accountability, and regulation quality indicators are not significant. Developmental expenditure and competitiveness are identified as key factors for promoting inclusive human development. Moreover, all three dimensions of governance enhance inclusive human development in selected Asian countries.